Purifikasi dan Karakterisasi Krom Reduktase Bacillus sp LKA9 - Ali, Alimuddin; Soetarto, Endang Sutariningsih; Widada, J. Sri (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
Chromate reductase is one of the potential enzymes for hexavalent chrom detoxification. Most of the enzyme is produced by bacteria, especially Bacillus. The aim of this research was to study chromate reductase activity isolated from Bacillus sp LKA9. Bacillus sp LKA9 was isolated from leather tannery liquid waste and used as a model in the experiment. Bacillus sp LKA9 was isolated through enrichment culture using Salt Base Solution containing 3 mM K2CrO4. Chromate reductase was isolated from bacteria by growing on a liquid medium containing chrom hexavalen (Cr VI) through several steps. The first step of the isolation process was to use the precipitated process using ammonium sulphate (30-80%). The next step, crude enzymes from the first step was partially purified through DEAE-Cellulose of Ion Exchange Chromatography Column. Diphenylcarbazide methods was used to examine the activity of enzyme fractions. The result of the experiment revealed that all protein could be precipitated by ammonium sulphate, and the cytoplasmic fraction at saturation of 50-70% showed high enzyme activity. Purified enzymes showed an increase activity 69,385 times to that of crude enzymes. The enzyme optimal had temperature and pH were 350C and 5; respectively. KM of enzyme was 0,0075 mM, and Vmax was 2500 ïmol/minute/mg protein. Enzyme activity was not inhibited by Cu2+, but an ion Ag2+ and Hg2+ inhibited the enzyme activity un-competitive. The activity of enzyme was demonstrated on SDS-PAGE by appearing typically band with molecular weight 29,26 kDa, it was assumed as chromate reductase.